Optimization od the Operation Behaviour of a Pemanent Magnet Excited Transverse Flux Motor for Direct Servo-Drive Applications Uve Werner - Wemer, U. (Scientific Journal of Gdynia Maritime University, 2017)
This paper presents a control based upon optimised current waveforms with switching on current harmonics to achieve an accurate position and speed control withreduced ripples in torque shape for a transverse flux motor. The approaches are verified by measured results at a two phase prototype of a magnet exicited transverse flux motor.